Mortality of the cassava mealybug Phenacoccus manihoti Mat.-Ferr.(Hom., Pseudococcidea) associated with an attack by Epidinocarsis lopezi (Hym., Encyrtidae) - Neuenschwander, Peter; Madojemu, E. (1986)
Cassava mealybugs (CM) of different stages, which had been stung by an E. lopezi female, were inspected after 6 and 20 days. The killing power of the parasitoid was several times higher than the production of parasitoid off-spring. Host-feeding and mutilation were responsible for 6-22% and 11-34% mortality respectively. Both were significantly more important on the younger hosts. 11-33% of the stung CM yielded live parasitoids. Reproduction was significantly more successful on older CM. 30-56% of all CM survived a single oviposition attempt by the wasp. By contrast, mortality of the unstung control was 4-8%. In choice experiments, 3rd instar CM were slightly but not significantly prefered.